NILAI PENDIDIKAN KARAKTER DALAM NOVEL SURGA YANG TAK DIRINDUKAN KARYA ASMA NADIA DAN IMPLIKASI TERHADAP PEMBELAJARAN TEKS NOVEL - Yanti, Yuli Dama; Asri, Yasnur; Hafrison, Mohd. (Universitas Negeri Padang, 2018)
This article was written to describe the value of character education contained in the novel Surga yang Tak Dirindukan of Asma Nadiaâ€™s work and the implication for the study of the text of the novel. This research is qualitative research with descriptive method. This research are words, phrases, and sentences that show the value of character education derived from the novel Surga yang Tak Dirindukan by Asma Nadia, published by Asma Nadia Publishing house Depok in June 2014. Based on the results of analyzing the found as many as 129 values of religious character education, 13 values of responsibility character education, 17 values of mutual character education, 13 values of education are polite, 19 values of charahter education curious, and 19 honest character education value. Based on the results of the discussion it can be seen that the results of this study can be implicated in novel text learning.Â Kata kunci: nilai, pendidikan karakter, novel Surga yang Tak Dirindukan